2016
DOI: 10.1523/jneurosci.4563-14.2016
|View full text |Cite
|
Sign up to set email alerts
|

ZIP It: Neural Silencing Is an Additional Effect of the PKM-Zeta Inhibitor Zeta-Inhibitory Peptide

Abstract: Protein kinase M (PKM), an atypical isoform of protein kinase C, has been suggested to be necessary and sufficient for the maintenance of long-term potentiation (LTP) and long-term memory (LTM). This evidence is heavily based on the use of inhibitory peptide (ZIP), a supposed specific inhibitor of PKM that interferes with both LTP and LTM. Problematically, both LTP and LTM are unaffected in both constitutive and conditional PKM knock-out mice, yet both are still impaired by ZIP application, suggesting a nonspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…There is an ongoing debate over whether the effect of ZIP on memory is due to PKM inhibition or if it results from nonspecific mechanisms of action (Lisman, 2012(Lisman, , 2017. Actually, PKM knock-out mice can form ZIP-sensitive memories (Lee et al, 2013;Volk et al, 2013) and ZIP induces seizures and reduces spontaneous hippocampal LFPs in anesthetized rats when used at concentrations 10 or more times higher than in our experiments (LeBlancq et al, 2016). At high concentrations, ZIP can also inhibit CaMKII and PKC/ (Pastalkova et al, 2006;Jalil et al, 2015), which can control AMPAR function and transport and compensate for PKM in PKM knock-out mice, respectively (Ren et al, 2013;Tsokas et al, 2016).…”
Section: Zip Does Not Affect Spontaneous Oscillatory Activity or Basamentioning
confidence: 55%
“…There is an ongoing debate over whether the effect of ZIP on memory is due to PKM inhibition or if it results from nonspecific mechanisms of action (Lisman, 2012(Lisman, , 2017. Actually, PKM knock-out mice can form ZIP-sensitive memories (Lee et al, 2013;Volk et al, 2013) and ZIP induces seizures and reduces spontaneous hippocampal LFPs in anesthetized rats when used at concentrations 10 or more times higher than in our experiments (LeBlancq et al, 2016). At high concentrations, ZIP can also inhibit CaMKII and PKC/ (Pastalkova et al, 2006;Jalil et al, 2015), which can control AMPAR function and transport and compensate for PKM in PKM knock-out mice, respectively (Ren et al, 2013;Tsokas et al, 2016).…”
Section: Zip Does Not Affect Spontaneous Oscillatory Activity or Basamentioning
confidence: 55%
“…Recent studies have shown that ZIP used for inhibiting PKMζ may also inhibit other atypical PKC isotypes such as PKCi/λ (29), and also that ZIP could alter neuronal and network activity in a way that might be independent of PKMζ (30,31). In addition, PKCi/λ can compensate PKMζ in certain conditions (29,32,33).…”
Section: Resultsmentioning
confidence: 99%
“…A recent example is the effect of knocking-out another second messenger molecule, PKM-ζ, in LTP. This was claimed as a landmark finding (Takeuchi et al 2014), but subsequent work showed that the knock-out altered other molecular and cellular effects besides PKM-ζ (see LeBlancq et al 2016), and produced unintended compensatory changes, thus weakening the claimed link (see Frankland and Josselyn 2016).…”
Section: Examples Of Psychoneural Reduction-the Cellular Basis Of Memorymentioning
confidence: 99%